Structure-based Versus Dynamic Usage-based Instruction: L2 French Writing skills after six years of instruction in high school. - Gombert, Wim; Keijzer, Merel; Verspoor, Marjolijn (Dutch Journal of Applied Linguistics, 2022)
In the Netherlands, teaching programs for French as a foreign language in secondary school usually involve an explicit focus on grammar. This is partially motivated by early findings in SLA research, which showed that explicit instruction is more effective in foreign language acquisition (Norris, & Ortega, 2000; Spada, & Tomita, 2010) and is even considered essential to achieve accuracy in advanced writing (Gunnarsson, 2012). The aim of this classroom study is to test these claims as it compares a structure-based (SB) method to a Dynamic Usage-Based (DUB) method in developing writing mastery in a pre-university program for French. The results suggest that both programs are equally effective in achieving grammatical accuracy and obtaining general text scores, but a DUB program seems more effective in achieving lexical complexity and fluency.